Analisis Tipe Perilaku Konsumen dalam Membeli Teh Celup - Setiyani, Rahmawati; Fitria, Annisa Vini; Asfarida, Tiara; Lestari, Retna Dewi (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2022)
The basic method used in this research is descriptive. The number of samples selected for analysis was 30 samples. The research technique used is a survey technique, namely research in which data collection takes samples from one population. Sampling was done using a random sampling technique (random sampling) on some tea bags consumers. The data used in this study is primary data. The involvement of consumers in the decision-making process of purchasing tea in Solo Raya is high, meaning that consumers are involved in evaluating the attributes of tea products to make the best decisions in purchasing tea products. These attributes include taste, scent, color, packaging, packaging design, content capacity, price, and distribution of tea products.